Executive functioning and reading achievement in school: a study of Brazilian children assessed by their teachers as “poor readers” - Engel de Abreu, Pascale M. J.; Abreu, Neander; Nikaedo, Carolina C.; Puglisi, Marina L.; Tourinho, Carlos J.; Miranda, Mônica C.; Befi-Lopes, Debora M.; Bueno, Orlando F. A.; Martin, Romain (Frontiers in Psychology, 2014)
This study examined executive functioning and reading achievement in 106 6- to 8-year-old Brazilian children from a range of social backgrounds of whom approximately half lived below the poverty line. A particular focus was to explore the executive function profile of children whose classroom reading performance was judged below standard by their teachers and who were carefully matched to controls on chronological age, sex, school type (Private or Public), domicile (Salvador/BA or São Paulo/SP), and socioeconomic status. Children completed a battery of 12 executive function tasks that were conceptually tapping cognitive flexibility, working memory, inhibition, and selective attention. Each executive function domain was assessed by several tasks. Principal component analysis extracted four factors that were labeled “Working Memory/Cognitive Flexibility”, “Interference Suppression”, “Selective Attention”, and “Response Inhibition”. Individual differences in executive functioning components made differential contributions to early reading achievement. The Working Memory/Cognitive Flexibility factor emerged as the best predictor of reading. Group comparisons on computed factor scores showed that the struggling readers presented limitations in Working Memory/Cognitive Flexibility, but not in other executive function components, compared to more skilled readers. These results validate the account that working memory capacity provides a crucial building block for the development of early literacy skills and extends it to a population of early readers of Portuguese from Brazil. The study suggests that deficits in working memory/cognitive flexibility might represent one contributing factor to reading difficulties in early readers which might have important implications for interventions for children at risk of school failure.